Oral health awareness and practices in pregnant females: A hospital-based observational study - Mayank Hans; Veenu Madaan Hans; Namrata Kahlon; Piyush Kumar Rameshchandra Ramavat; Usha Gupta; Asim Das (Wolters Kluwer Medknow Publications, 2019)
Background: The aim of this study was to assess the oral health awareness, methods adopted to maintain hygiene, prevalent myths regarding oral health in pregnancy, and importance of oral health during pregnancy, to help formulate oral health program for pregnant females in partaking hospital. Materials and Methods: A total of 225 pregnant females participated in the study. After complete demographic assessment of participants, a questionnaire was provided to them. Questionnaire included simple multiple choice questions on how they maintained oral hygiene, their oral health status, visit to the dentist, and barriers in seeking treatment. This was followed by a questionnaire regarding common myths and understanding of the importance of oral health during pregnancy which had three choices: true, false, and do not know. The results were expressed in percentages, and one sample t-test for percentages was applied where ever required. Results: Majority of participants self-reported some form of oral health problems with bleeding gums as a chief complaint leading the survey. Around half of the participants had never visited a dentist, and an abundant number of pregnant females reported safety concerns for developing the child as a reason for not taking any treatment during pregnancy. A highly significant number of participants were unaware of the importance of oral health during pregnancy and believed in age-old myths. Conclusion: The oral health care still remains on the backseat in care provided to pregnant female. A complete overhaul of understanding through individual, family, and community counseling is required to spread awareness.